Dynamics in the Impact of Entrepreneurship Orientation on Corporate the Moderating Role of Environmental Performance - Zhen, Liu; Ali, Dhakir Abbas (Journal of Ecohumanism, 2024)
This study examines the impact of environmental dynamics on the relationship between Entrepreneurial Orientation (EO) and corporate performance in the Malaysian aviation industry, specifically investigating the mediating effect of environmental performance. The focus is on the influence of technological advancement, economic policy reorientation, and political and security stability on EO, as documented by Hina et al. (2020) and Haider et al. (2017), in relation to business performance. Additionally, the study explores the effect of environmental dynamism on this relationship. A quantitative approach was adopted, collecting data from 100 staff members of three selected Chinese airlines. The findings show a high correlation between EO and variables such as technological innovations, economic policy reforms, political stability, and security. It is confirmed that environmental changes positively influence the relationship between EO and business performance. The results suggest that companies with a higher level of EO are more competent in managing technology, adjusting economic policies, and thriving in politically and security-stable environments. This study offers valuable insights for strategic decision-making in the aviation industry, emphasizing the importance of fostering entrepreneurial behaviour and adaptive capacities to enhance organizational performance within dynamic business environments.